The possibilities of silymarin extract use in alcoholic liver disease – a literature review - Aleksandra Kołota (Alcoholism and Drug Addiction, 2017)
The development of alcoholic liver disease (ALD), characterised by different degrees of liver damage, may be one of the possible effects of the long-term, excessive alcohol consumption. The treatment is based on total abstinence, which affects a significant mortality reduction and on nutritional therapy associated with excessive weight loss and muscle atrophy prevention, as well as reducing vitamin and mineral deficiency, especially as these patients are very often at risk of malnutrition. Ethanol transformation in the body leads to the free radical production, which generates so called oxidative stress. As this is considered the main factor in the liver damage, researchers have been trying to identify substances that could have a significant effect on oxidative stress reduction. The aim of the study was to define the possibility of applying the silymarin extract from seeds of milk thistle as a supporting element in the nutritional treatment of alcoholic liver disease and to characterise its potential adverse effects based on the currently available literature. Studies conducted in groups of patients at various stages of alcoholic liver disease provide ambiguous results. This may be due to the applied time and dosage of the silymarin extract, due to the fact that its components are characterised by low water and fats solubility, as well as low re-absorption in the intestine. It is also possible that bioavailability is influenced by the patient’s nutritional state. However, in experiments applied in various laboratory animal models, most of the results indicated that the silymarin first of all normalises liver enzyme levels, has also a positive influence on the parameters of antioxidative defense, reduces lipid peroxidation and inhibits the production of inflammatory response mediators. It is especially important that no side effects were observed during use of the silymarin extract in any study. It may be concluded that alcoholic liver disease patients may experience some benefits while using silymarin extract, especially given that all studies confirmed its safety.